Combined effects of biochar and fertilizer application on maize production in dependence on the cultivation method in a sub-humid climate. Issue 22 (16th December 2018) - Graef, H.; Kiobia, D.; Saidia, P.; Kahimba, F.; Graef, F.; Eichler-Löbermann, B.
ABSTRACT: Low, erratic rainfall amounts and restricted accessibility of chemical fertilizer for rural farmers in developing countries may have negative effects on crop production. Agricultural methods like biochar applications, fertilizer microdosing and tied ridging can help to mitigate these constraints, but have rarely been studied in combination and under varying water availability. A field trial was conducted in split-plot design over two contrasting cropping seasons in 2016 and 2017 in Tanzania to study the effect of these agricultural methods on maize grain yield, biomass, leaf area index, plant height and soil moisture content. In both seasons each with contrasting irrigation frequencies, fertilizer microdosing increased the grain yield of maize. Biochar alone affected the yield only at high application rates (10 t/ha) and low irrigation frequency. However, when combined with fertilizer microdosing the yield effect of biochar was more pronounced. For example, combining 5 t/ha biochar with fertilizer microdosing under flat tillage increased yield by 170% compared to the control without biochar and fertilizers. Tied ridges increased soil moisture content and tended to increase maize yield compared to flat tillage, whereas biochar application resulted in significantly higher soil moisture contents. Fertilizer microdosing with biochar application can be recommended to improve maize yields mainly under flat tillage.